Dentin/composite bond strength: effect of aging and experimental unit - Lima, Julia Magalhães Costa [UNESP]; Anami, Lilian Costa [UNESP]; Pereira, Sarina Maciel Braga [UNESP]; de Melo, Renata Marques [UNESP]; Bottino, Marco Antonio [UNESP]; de Miranda, Larissa Mendonça; Souza, Karina Barbosa; Özcan, Mutlu; Souza, Rodrigo Othávio Assunção (Taylor & Francis, 2020)
The objective of this study was to compare bond strengths between composite and dentin using different adhesive systems and to assess the influence of the experimental unit during thermocycling. Ninety recently extracted human molars were selected, and the occlusal third of each crown was removed. The teeth were divided into 15 groups (n = 6), according to the type of adhesive (1, 2, or 3 steps), the aging conditions (dry, distilled water storage, or thermocycling), and the experimental unit used during aging (sticks or blocks). On occlusal surfaces, composite blocks were constructed. Specimens from the “blocks” experimental units were aged as blocks and then cut into sticks, while specimens from the “sticks” experimental units were cut before being aged. The microtensile bond strength test was performed and the failure types were classified. Data were statistically analyzed. The type of adhesive was the only variable that significantly influenced the bond strength among tested groups (p =.0024). Lower values were obtained for the specimens cemented with the 3-step adhesive and thermocycled before being cut (p =.0024), while the highest values were obtained for the 2-step adhesive thermocycled as sticks. Dunnett's test showed that the group differing from the dry subgroups (control) was that with the 3-step adhesive thermocycled as blocks. The predominant failure mode was the cohesive failure of the composite resin. It can be concluded that the different adhesive systems applied to dentin demonstrated similar bond strength, except for the 3 and 2-step adhesives after thermocycling. Moreover, the aging protocols and the experimental unit did not influence the µTSB.
Keywords: Adhesives; aging; dentin-bonding agents; tensile strength